Toward unbiased flow measurements in LHC proton-proton collisions - Kallio, Teemu (2024)
Two-particle angular correlations of charged-particle pairs are studied in pp collisions at √s = 13 TeV with four different Monte-Carlo event generators. Correlation functions are constructed with relative azimuthal angle ∆φ and relative pseudorapidity distance ∆η between hadrons such as π, K, p and Λ particle pairs in multiple ∆η intervals. Using the low-multiplicity template fit method, enhanced jet yields in high-multiplicity events with respect to low-multiplicity events are subtracted. Due to a kinematic bias from jets and the difference in how event generators implement jet and flow components, subtraction of non-flow bias results in small systems. With a multiphase transport (AMPT) string melting model mass ordering of the extracted flow coefficients at low-pT and particle type grouping at high-pT ranges was observed. However, these characteristics are found to be different from results observed in large systems.